Un estudio de la colección y mantenimiento del germoplasma de yucas silvestres, Manihot spp. - Nassar, N.M.A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
An urgent effort to conserve genetic resources of wild cassava is badly needed. Occurence of wild cassava species in their natural habitats is dimininshing day after day and a number of species are on the verge of extinction. Trials of collecting these wild species from their natural habitats were carried out. Frequency of their occurence in these habitats is reported. By experimenting with different ways of preserving these species, it was found that transplanting whole plants is the most efficient method of reproducing the sub-shruby species. Grafting scions of wild shruby species onto stocks of cassava was found to be another potential way of germplasm conservation